AKRONIM YANG BERFONOTAKTIK TIDAK LAZIM DALAM BAHASA INDONESIA - NFN Sariah (Linguistik Indonesia, 2014)
This acronym research describes some uncommon phonotactic acronyms in Indonesian. Three indicators were used as guidance: (1) the list of phonotactic phonemes, (2) the common closed consonants, (3) the number of common syllables in Indonesian. The data were taken from national news papers from January 2012 thorugh March 2013. The results indicated: (1) uncommon phonotactic acronyms were usually found in the phoneme list of /md/ for Gakumdu, /nm/ for menmud, the /pk/ for Apkasi, and /pm/ for ipmi. (2) The acronyms of two identical sequenced consonants were found in the consonants /pp/ as in Bappepti, /ss/ in Kopassus, /mm/ in jamman, and /tt/ in Unpatti. (3) The acronyms of double consonant were found in the consonants /dh/ as in pusbadhi, /ngg/ in unpatti, and /nd/ in unand. The acronyms containing consonanst that were not used as word-closing acronyms were the consonants /g/ and /d/. The closing word consonant /c/ was not found in the data. Besides, acronyms using closed word consonants were found in the consonants /z/ and /v/. In borrowed words the consonants that were not found were /z/ and /v/ as word-closing acronyms, such as in baznas, pemprov. The repetition of similar phonemes in some syllables was found in riskesdas. The number of syllables commonly found in Indonesian acronyms consisted of four or more words, for example, babinkumnas, ditreskrimsus.